The horrible in nature reflects our worth: An investigation into the connection between Kant's notion of the sublime and our moral personhood - Thomson, Michael H. (My University, 2000)
The purpose of this thesis is to investigate Immanuel Kant's experience of the sublime and its reference to our moral personhood. I argue that when we contemplate the infinitely powerful in nature manifest in hurricanes, raging seas, etc., we are moved toward our moral nature and our infinite moral vocation. We come to esteem our rational power for moral lawfulness and autonomy in contrast to our more basic physical being. I also investigate what possible path an individual might be expected to pursue given that they embrace their moral nature. I argue that we adopt a disposition that orients us positively toward others and seeks a community of shared ends that contribute to the welfare and promotion of humanity.
Keywords: Philosophy; Philosophy